1993
DOI: 10.1192/bjp.163.2.195
|View full text |Cite
|
Sign up to set email alerts
|

How Well are ‘Cured’ Anorexia Nervosa Patients?

Abstract: Eating behaviour, nutritional intake and psychopathology were examined in 16 weight-recovered anorexia nervosa patients. The Eating Disorders Examination (EDE) and a food diary were the main outcome measures, but body fat content and psychosocial adjustment were also assessed. Although body fat and overall psychosocial adjustment had returned to normal in most patients, 12 still had a restricted eating pattern with nutritional intake below 90% of their energy requirements. These results suggest that weight, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…Several studies have demonstrated the risks of defining recovery only by physical and behavioral criteria and not taking the individual’s psychological functioning into account. The persistence of anorexic cognitions and food restriction after normalizing weight [65] and the high levels of depression, anxiety, and obsessional behavior among adolescents who have “recovered” from AN [66] may produce instead a pseudorecovery , that is, a physical recovery but with the psychological components of AN unchanged [67] and therefore a high risk of relapse [68]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the risks of defining recovery only by physical and behavioral criteria and not taking the individual’s psychological functioning into account. The persistence of anorexic cognitions and food restriction after normalizing weight [65] and the high levels of depression, anxiety, and obsessional behavior among adolescents who have “recovered” from AN [66] may produce instead a pseudorecovery , that is, a physical recovery but with the psychological components of AN unchanged [67] and therefore a high risk of relapse [68]. …”
Section: Discussionmentioning
confidence: 99%
“…For most patients suffering from severe anorexia nervosa (AN) hospitalization does not lead to full remission, but long-term therapeutic involvement is required, inasmuch as in many of these patients a wide range of residual psychopathological features persist after weightrecovery (Windauer et al, 1993;Bastiani et al, 1995;Eckert et al, 1995;Herpertz-Dahlmann et al, 1996). Research ®ndings on the long-term course of AN suggest that a signi®cant percentage of individuals successfully treated in hospital experience a worsening of symptoms after discharge, prior to recovery (Theander, 1970;Eckert et al, 1995;Strober et al, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…For example, Windauer, Lennerts, Talbot, Touyz and Beumont (1993) have demonstrated that in a majority of patients whose weight had returned to normal, marked eating and other problems persisted. The Morgan and Russell outcome scales and scores (1975) allov/ for more specific outcome measures.…”
Section: Outcomementioning
confidence: 99%